Expression of E- and N-cadherins in tumor in luminal, primary operable breast cancer without Her2/neu overexpression in postmenopausal women as a prognostic factor - V. V. Tokmakov; E. P. Ulianova; Yu. S. Shatova; A. B. Sagakyants; N. M. Mashchenko; I. A. Novikova; E. M. Nepomnyashchaya; O. G. Shulgina (Исследования и практика в медицине, 2020)
Purpose of the study. Evaluation of the expression of E- and N-cadherins in tumor tissues in postmenopausal patients with primary operable luminal breast cancer (BC) without Her2/neu overexpression for inclusion in the panel of a comprehensive assessment of tumor biological parameters for the disease prognosis.Patients and methods. The study included 120 patients divided into two groups: patients with luminal A and luminal B subtypes. To evaluate the prognostic significance of E- and N- cadherins in both groups of patients, we analyzed expression levels and correlation using the Mann- Whitney U-test and Spearman correlation criterion; overall survival, progression-free and tumor- specific one, at various values of the studied biomarkers — by the Kaplan- Meier method.Results. The differences in the mean expression levels were not statistically significant (p>0,05). E-cadherin was twice higher in luminal A BC (55.4±5.2) compared to luminal B BC (28.1±4.9), N-cadherin in luminal A BC (12.8±5.3) was 1.3 times lower than in luminal B BC (17.06±5.4). Patients with luminal B BC demonstrated a tendency to the loss of E-cadherin and increased expression of N-cadherin, which is often associated with poor prognosis. However, the correlation between these markers was not statistically significant (p>0,05).Conclusions. Thus, despite the differences in levels of E- and N-cadherin expression, these markers did not show their prognostic significance, and therefore, they were not included in the panel for a comprehensive assessment of tumor biological parameters when determining the prognosis of luminal breast cancer without Her2/neu overexpression in postmenopausal women.